Dynamic characteristics analysis for a new-type maglev vehicle. (December 2017) - Wang, Keren; Luo, Shihui; Ma, Weihua; Chen, Xiaohao
A new type of walking mechanism for middle- and low-speed maglev vehicle, including a single anti-roll beam placed at the middle of each suspension frame, a big air spring placed at the middle of each longitudinal beam of each suspension module, and a forced steering mechanism canceled, was proposed to improve the comprehensive competitiveness of the middle- and low-speed maglev vehicle in the field of urban rail transit. The dynamic characteristics of a new-type maglev vehicle were investigated by dynamics simulation analysis. The following conclusions are drawn based on the obtained results: the new-type maglev vehicle meets the operational requirements at the running speed of 160 km/h on the straight line and at the running speed of 30 km/h on the curved track of radius 75 m.